Vaginal natural orifice transluminal endoscopic surgery (vNOTES): a new chapter in vaginal surgical innovation - Sarah Wylie; Eric Mutema; Wai Yoong (Journal of Obstetrics and Gynaecology)
Vaginal Natural Orifice Transluminal Endoscopic Surgery (vNOTES) is a novel minimal invasive technique which employs the vaginal orifice for surgical access, after which endoscopic instruments are introduced, thus obviating the need for any external skin incisions. This approach has gained traction as it is associated with reduced morbidity, improved cosmesis, lower pain scores and decreased length of hospital stay, with no increase in adverse events, when compared with conventional laparoscopic surgery. Initially limited to hysterectomy and adnexectomy, its role has now expanded to include indications such as urogynaecology, oncology and fertility. Clinicians wishing to implement vNOTES need to undergo appropriate training and appreciate judicious governance. Further randomised controlled trials will allow us to better understand if this newer technique will offer well-evidenced preferable outcomes and become the preferred surgical approach.